Composition for forming resist underlayer film using cyclic carbonyl compound

By using the resist lower film formation composition containing aromatic compounds and cyclic carbonyl compounds, the problems of poor coating properties of the high and low difference substrate and uneven film are solved, high etch resistance and good dry etching speed ratio are achieved, and it is suitable for substrate processing with high fineness.

CN112166379BActive Publication Date: 2025-04-01NISSAN CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980035022.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-05-25
Filing Date
2019-05-21
Publication Date
2025-04-01
Estimated Expiration
2039-05-21

AI Technical Summary

Technical Problem

In the prior art, when forming a resist lower layer film, it is difficult to achieve good coating properties of the high and low substrate and small film thickness differences, resulting in uneven film films and making it difficult to achieve high fine substrate processing.

Method used

A resist film formation composition containing an aromatic compound having 6 to 60 carbon atoms, a cyclic carbonyl compound and a reaction product and a reaction product is used to form a lower film having high etch resistance and good dry etching speed ratio by combining a specific reaction product and a solvent.

Benefits of technology

Good coating properties for the high and low difference substrate are achieved, the film thickness difference is small, and a flat film is formed, which improves the fineness of substrate processing, and is suitable for the manufacturing of multi-layer resist processes and semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002795602520000031
    Figure BDA0002795602520000031
  • Figure BDA0002795602520000032
    Figure BDA0002795602520000032
  • Figure BDA0002795602520000081
    Figure BDA0002795602520000081
Patent Text Reader

Abstract

Provided is a composition for forming a resist underlayer film, which exhibits high etching resistance, good dry etching rate ratio and optical constants, has good coverage even on so-called uneven substrates, has a small difference in film thickness after embedding, and can form a flat film. In addition, provided are a method for producing a polymer suitable for the composition for forming a resist underlayer film, a resist underlayer film using the composition for forming a resist underlayer film, and a method for producing a semiconductor device. A composition for forming a resist underlayer film, comprising: an aromatic compound (A) having 6 to 60 carbon atoms, a reaction product of a carbonyl group possessed by a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; and a solvent, wherein in the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two of the aromatic compounds (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for forming an anti-etching underlayer film, which exhibits high etching resistance, good dry etching rate ratio and optical constants, has good coverage even on so-called uneven substrates, has a small difference in film thickness after embedding, and can form a flat film, a method for producing a polymer suitable for the composition for forming an anti-etching underlayer film, a resist underlayer film using the composition for forming an anti-etching underlayer film, and a method for producing a semiconductor device. Background Art

[0002] In recent years, resist underlayer film materials used in multilayer resist processes have been required to function as antireflective films, particularly for short-wavelength exposure, have appropriate optical constants, and also have etching resistance in substrate processing, and the use of polymers having repeating units containing benzene rings has been proposed (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2004-354554 Summary of the invention

[0006] Problems to be solved by the invention

[0007] It is known that due to the thin filmization of the resist layer required with the miniaturization of the resist pattern, at least two layers of resist lower films are formed, and the resist lower films are used as a photolithography process of a mask material. It is a method of arranging at least one organic film (lower organic film) and at least one inorganic lower film on a semiconductor substrate, using the resist pattern formed on the upper resist film as a mask to pattern the inorganic lower film, and using the pattern as a mask to pattern the lower organic film, it is generally believed that a pattern with a high aspect ratio can be formed. As the material forming the above-mentioned at least two layers, a combination of an organic resin (for example, an acrylic resin, a novolac resin) and an inorganic material (silicone resin (for example, an organopolysiloxane), an inorganic silicon compound (for example, SiON, SiO2) etc.) can be cited. Further in recent years, a double patterning technique of performing two photolithography and two etchings in order to obtain one pattern has been widely used, and the above-mentioned multilayer process has been used in each process. At this time, it is generally considered that the organic film formed after the initial pattern is formed needs a property of flattening the height difference.

[0008] However, for a so-called uneven substrate in which the resist pattern formed on the substrate has height differences and density, the resist underlayer film-forming composition has low coverage, and the film thickness difference after embedding becomes large, making it difficult to form a flat film.

[0009] The present invention is proposed based on solving such problems, and its purpose is to provide a resist underlayer film-forming composition which shows high etching resistance, good dry etching rate ratio and optical constants, has good coverage even on so-called uneven substrates, has a small film thickness difference after embedding, and can form a flat film. Another purpose of the present invention is to provide a method for producing a polymer suitable for the resist underlayer film-forming composition, a resist underlayer film using the resist underlayer film-forming composition, and a method for producing a semiconductor device.

[0010] Means for solving problems

[0011] The present invention includes the following aspects.

[0012] [1] A composition for forming a resist underlayer film, comprising: a reaction product of an aromatic compound (A) having 6 to 60 carbon atoms and a carbonyl group possessed by a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; and a solvent,

[0013] The cyclic carbonyl compound (B) contains 5% by mass or more of heteroatoms,

[0014] In the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two aromatic compounds (A).

[0015] [2] The resist underlayer film forming composition according to [1], wherein the cyclic carbonyl compound (B) has at least 4 hetero atoms in one molecule.

[0016] [3] The resist underlayer film forming composition according to [1] or [2], wherein the cyclic carbonyl compound (B) is represented by the following formula (1).

[0017]

[0018] [Wherein,

[0019] X is O, NH, or CH2,

[0020] Ring Y is a three- to eight-membered ring which may have the following groups as substituents and may be interrupted by heteroatoms, or a connected ring or condensed ring thereof: an alkyl group having 1 to 20 carbon atoms, which may be substituted by a hydroxyl group or a carbonyl group and may be interrupted by an oxygen atom or a sulfur atom, a hydroxyl group, an oxo group, a carboxyl group, a cyano group, a nitro group, a sulfo group, an acyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 1 to 6 carbon atoms, an amino group, a glycidyl group, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms.]

[0021] [4] A composition for forming a resist underlayer film, comprising: a reaction product of an aromatic compound (A) having 6 to 60 carbon atoms and a carbonyl group possessed by a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; and a solvent,

[0022] The cyclic carbonyl compound (B) is represented by the following formula (1).

[0023]

[0024] [Wherein,

[0025] X is CH2,

[0026] Ring Y is a three- to eight-membered ring which may have the following groups as substituents, or a connected ring thereof: an alkyl group having 1 to 20 carbon atoms, which may be substituted by a hydroxyl group or a carbonyl group and may be interrupted by an oxygen atom or a sulfur atom, a hydroxyl group, an oxo group, a carboxyl group, a cyano group, a nitro group, a sulfo group, an acyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 1 to 6 carbon atoms, an amino group, a glycidyl group, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms.]

[0027] [5] The resist underlayer film forming composition according to [4], wherein in the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two of the aromatic compounds (A).

[0028] [6] The resist underlayer film forming composition according to any one of [3] to [5], wherein the cyclic carbonyl compound (B) is an alicyclic compound.

[0029] [7] The resist underlayer film forming composition according to any one of [1] to [6], wherein the cyclic carbonyl compound (B) does not contain a benzene ring.

[0030] [8] The resist underlayer film forming composition according to any one of [1] to [7], wherein the compound (A) contains one or more benzene rings, naphthalene rings, anthracene rings, pyrene rings, or a combination thereof.

[0031] [9] The resist underlayer film forming composition according to any one of [1] to [7], wherein the compound (A) contains two or more benzene rings, naphthalene rings, anthracene rings, pyrene rings, or a combination thereof.

[0032]

[10] The resist underlayer film forming composition according to any one of [1] to [9], further comprising a crosslinking agent.

[0033]

[11] The resist underlayer film forming composition according to any one of [1] to

[10] , further comprising an acid and / or an acid generator.

[0034]

[12] The resist underlayer film forming composition according to any one of [1] to

[11] , wherein the boiling point of the solvent is 160° C. or higher.

[0035]

[13] A resist underlayer film characterized by being a fired product of a coating film formed from the resist underlayer film forming composition according to any one of [1] to

[12] .

[0036]

[14] A method for manufacturing a semiconductor device, comprising the following steps: a step of forming a resist underlayer film on a semiconductor substrate using the resist underlayer film forming composition described in any one of [1] to

[12] ; a step of forming a resist film on the above-mentioned resist underlayer film; a step of forming a resist pattern by irradiating and developing with light or electron beams; a step of etching the underlayer film using the resist pattern; and a step of processing the semiconductor substrate using the patterned underlayer film.

[0037]

[15] A method for producing a polymer for a resist underlayer film-forming composition, comprising the steps of: reacting an aromatic compound (A) having 6 to 60 carbon atoms with a carbonyl group of a cyclic carbonyl compound (B) having 3 to 60 carbon atoms;

[0038] In the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two aromatic compounds (A).

[0039]

[16] A method for producing a polymer for a resist underlayer film-forming composition, comprising the steps of: reacting an aromatic compound (A) having 6 to 60 carbon atoms with a carbonyl group of a cyclic carbonyl compound (B) having 3 to 60 carbon atoms;

[0040] The cyclic carbonyl compound (B) contains 5% by mass or more of heteroatoms,

[0041] In the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two aromatic compounds (A).

[0042] Effects of the Invention

[0043] The resist underlayer film forming composition of the present invention not only has high etching resistance, good dry etching rate ratio and optical constants, but also the obtained resist underlayer film has good coverage on the so-called uneven substrate, and the film thickness difference after embedding is small, forming a flat film, thereby realizing finer substrate processing.

[0044] In particular, the resist underlayer film-forming composition of the present invention is effective for a photolithography process in which at least two resist underlayer films are formed for the purpose of reducing the resist film thickness and the resist underlayer films are used as etching masks. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a diagram for explaining Iso-dense bias. Figure 1 The (ba) in is the Iso-dense deviation. DETAILED DESCRIPTION

[0046] [Resist underlayer film forming composition]

[0047] The resist underlayer film forming composition of the present invention comprises: a reaction product of an aromatic compound (A) having 6 to 60 carbon atoms and a carbonyl group of a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; a solvent; and other components. These components are described in order below.

[0048] [Aromatic compound having 6 to 60 carbon atoms (A)]

[0049] Aromatic compounds with 6 to 60 carbon atoms (A)

[0050] (a) may be a monocyclic compound such as benzene, phenol, or phloroglucinol,

[0051] (b) may be a fused ring compound such as naphthalene or dihydroxynaphthalene,

[0052] (c) may be a heterocyclic compound such as furan, thiophene, pyridine or carbazole,

[0053] (d) may be a compound in which the aromatic rings of (a) to (c) are bonded via a single bond, such as biphenyl, phenylindole, 9,9-bis(4-hydroxyphenyl)fluorene, and α,α,α',α'-tetrakis(4-hydroxyphenyl)-p-xylene.

[0054] (e) may be phenylnaphthylamine, wherein the aromatic rings of (a) to (d) are connected by -CH-, -(CH2) n A compound in which a spacer group exemplified by -(n=1 to 20), -CH=CH-, -CH≡CH-, -N=N-, -NH-, -NHR-, -NHCO-, -NRCO-, -S-, -COO-, -O-, -CO- and -CH=N- is linked.

[0055] Examples of the aromatic compound include benzene, thiophene, furan, pyridine, pyrimidine, pyrazine, pyrrole, Azoles, thiazoles, imidazoles, naphthalene, anthracene, quinoline, carbazole, quinazoline, purine, indolizine, benzothiophene, benzofuran, indole, phenylindole, acridine, etc.

[0056] Furthermore, the aromatic compound (A) may be an aromatic compound containing an amino group, a hydroxyl group, or both. Furthermore, the aromatic compound (A) may be an arylamine compound, a phenol compound, or an aromatic compound containing both.

[0057] An aromatic amine or a compound containing a phenolic hydroxyl group is preferred.

[0058] Examples of the aromatic amine include aniline, diphenylamine, phenylnaphthylamine, hydroxydiphenylamine, phenylnaphthylamine, N,N′-diphenylethylenediamine, and N,N′-diphenyl-1,4-phenylenediamine.

[0059] Examples of the compound containing a phenolic hydroxyl group include phenol, dihydroxybenzene, trihydroxybenzene, hydroxynaphthalene, dihydroxynaphthalene, trihydroxynaphthalene, tris(4-hydroxyphenyl)methane, tris(4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, and polynuclear phenol.

[0060] Examples of the polynuclear phenol include dihydroxybenzene, trihydroxybenzene, hydroxynaphthalene, dihydroxynaphthalene, trihydroxynaphthalene, tris(4-hydroxyphenyl)methane, tris(4-hydroxyphenyl)ethane, 2,2′-biphenol, and 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane.

[0061] The hydrogen atoms of the aromatic compound (A) having 6 to 60 carbon atoms may be substituted with an alkyl group having 1 to 20 carbon atoms, a condensed ring group, a heterocyclic group, a hydroxyl group, an amino group, a nitro group, an ether group, an alkoxy group, a cyano group, or a carboxyl group.

[0062] Examples of the alkyl group having 1 to 20 carbon atoms include linear or branched alkyl groups which may or may not have a substituent, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, n-octyl, cyclohexyl, 2-ethylhexyl, n-nonyl, isononyl, p-tert-butylcyclohexyl, n-decyl, n-dodecylnonyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and eicosyl. An alkyl group having 1 to 12 carbon atoms is preferred, an alkyl group having 1 to 8 carbon atoms is more preferred, and an alkyl group having 1 to 4 carbon atoms is further preferred.

[0063] Examples of the alkyl group having 1 to 20 carbon atoms interrupted by an oxygen atom, a sulfur atom or an amide bond include groups containing the structural unit -CH2-O-, -CH2-S-, -CH2-NHCO- or -CH2-CONH-. -O-, -S-, -NHCO- or -CONH- may have one unit or two or more units in the alkyl group. Specific examples of the alkyl group having 1 to 20 carbon atoms interrupted by -O-, -S-, -NHCO- or -CONH- units include methoxy, ethoxy, propoxy, butoxy, methylthio, ethylthio, propylthio, butylthio, methylcarbonylamino, ethylcarbonylamino, propylcarbonylamino, butylcarbonylamino, methylaminocarbonyl, ethylaminocarbonyl, propylaminocarbonyl, butylaminocarbonyl, and the like, and further include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, or octadecyl, and each of which is substituted by methoxy, ethoxy, propoxy, butoxy, methylthio, ethylthio, propylthio, butylthio, methylcarbonylamino, ethylcarbonylamino, methylaminocarbonyl, ethylaminocarbonyl, and the like. Preferred are methoxy, ethoxy, methylthio, and ethylthio, and more preferred are methoxy and ethoxy.

[0064] The fused ring group is a substituent derived from a fused ring compound, and specific examples thereof include phenyl, naphthyl, anthracenyl, phenanthrenyl, naphthacene, benzo[9,10]phenanthrenyl, pyrenyl, and Among them, phenyl, naphthyl, anthracenyl and pyrenyl are preferred.

[0065] The heterocyclic group is a substituent derived from a heterocyclic compound, and specific examples thereof include thienyl, furyl, pyridyl, pyrimidyl, pyrazinyl, pyrrolyl, oxazolyl, thiazolyl, imidazolyl, quinolyl, carbazolyl, quinazolinyl, purinyl, indolizinyl, benzothiophenyl, benzofuranyl, indolyl, acridinyl, isoindolyl, benzimidazolyl, isoquinolyl, quinoxalinyl, cinnolinyl, pteridinyl, chromenyl (benzopyranyl), isochromenyl (benzopyranyl), xanthenyl, thiazolyl, pyrazolyl, imidazolinyl, oxazinyl, among which thienyl, furanyl, pyridinyl, pyrimidinyl, pyrazinyl, pyrrolyl, oxazolyl, thiazolyl, imidazolyl, quinolyl, carbazolyl, quinazolinyl, purinyl, indolizinyl, benzothiophenyl, benzofuranyl, indolyl and acridinyl, most preferably thiophenyl, furanyl, pyridyl, pyrimidinyl, pyrrolyl, oxazolyl, thiazolyl, imidazolyl and carbazolyl.

[0066] In addition, the above aromatic compounds may be linked via a single bond or a spacer.

[0067] Examples of the spacer group include -CH-, -(CH2) n-(n=1-20), -CH=CH-, -CH≡CH-, -N=N-, -NH-, -NHR-, -NHCO-, -NRCO-, -S-, -COO-, -O-, -CO- and -CH=N-, or a combination of two or more thereof. Two or more of these spacers may be linked together.

[0068] The aromatic compound (A) preferably contains one or more benzene rings, naphthalene rings, anthracene rings, pyrene rings or a combination thereof, and more preferably contains two or more benzene rings, naphthalene rings, anthracene rings, pyrene rings or a combination thereof.

[0069] The aromatic compound (A) may be one or more kinds, and preferably one or two kinds.

[0070] [Cyclic carbonyl compound having 3 to 60 carbon atoms (B)]

[0071] The cyclic carbonyl compound (B) having 3 to 60 carbon atoms is a compound in which two of the above aromatic compounds (A) are linked to one carbon atom of the cyclic carbonyl compound (B).

[0072] The cyclic carbonyl compound (B) preferably contains 5% by mass or more of heteroatoms, more preferably 10% by mass or more of heteroatoms. In addition, the cyclic carbonyl compound (B) preferably does not contain a benzene ring.

[0073] Examples of heteroatoms include nitrogen, oxygen, sulfur, phosphorus, and halogens. The cyclic carbonyl compound (B) preferably has at least one heteroatom in one molecule. Preferably, it has at least two heteroatoms in one molecule. Preferably, it has at least three heteroatoms in one molecule. Preferably, it has at least four heteroatoms in one molecule.

[0074] The cyclic carbonyl compound (B) is preferably represented by the following formula (1).

[0075]

[0076] [Wherein,

[0077] X is O, NH, or CH2,

[0078] Ring Y is a three- to eight-membered ring which may have the following groups as substituents and may be interrupted by heteroatoms, or a connected ring or condensed ring thereof: an alkyl group having 1 to 20 carbon atoms, which may be substituted by a hydroxyl group or a carbonyl group and may be interrupted by an oxygen atom or a sulfur atom, a hydroxyl group, an oxo group, a carboxyl group, a cyano group, a nitro group, a sulfo group, an acyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 1 to 6 carbon atoms, an amino group, a glycidyl group, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms.]

[0079] The alkyl group having 1 to 20 carbon atoms is as described above. Examples of the acyl group having 1 to 6 carbon atoms include formyl and acetyl. Examples of the alkoxy group having 1 to 6 carbon atoms include methoxy, ethoxy, n-propoxy, isopropoxy, and the like. Examples of the alkoxycarbonyl group having 1 to 6 carbon atoms include methoxycarbonyl, ethoxycarbonyl, n-propoxycarbonyl, isopropoxycarbonyl, and the like. Examples of the aryl group having 6 to 20 carbon atoms include phenyl, o-methylphenyl, m-methylphenyl, p-methylphenyl, o-methoxyphenyl, p-methoxyphenyl, α-naphthyl, β-naphthyl, o-biphenyl, m-biphenyl, p-biphenyl, 1-anthryl, 2-anthryl, 9-anthryl, 1-phenanthrenyl, 2-phenanthrenyl, 3-phenanthrenyl, 4-phenanthrenyl, 9-phenanthrenyl, and fluorenyl. Examples of the alkenyl group having 2 to 10 carbon atoms include vinyl and allyl. Examples of the alkynyl group having 2 to 10 carbon atoms include ethynyl and the like. The hetero atom, cyclic compound, linked ring and condensed ring are as described above.

[0080] The cyclic carbonyl compound (B) is preferably an alicyclic compound. The cyclic carbonyl compound (B) may be one or more, and is preferably one or more.

[0081] Some particularly preferred examples of the cyclic carbonyl compound (B) include dehydrocholic acid, cortisone acetate, gluconolactone, camphorsulfonic acid, arabinose ascorbic acid, isocyanuric acid and its derivatives (e.g., diallyl isocyanurate, monoallyl isocyanurate, mono-n-butyl isocyanurate), tricyclo[5.2.1.0 2,6 ]Decan-8-one, dicyclohexane-4,4'-dione monoethylene glycol ketal, 1,4-cyclohexanedione monoethylene glycol ketal, 2-adamantanone, cyclohexanone, 2-cyclopentylcyclopentanone, and 2-cyclohexylcyclohexanone.

[0082] [Reaction product]

[0083] By reacting the aromatic compound (A) with the carbonyl group of the cyclic carbonyl compound (B), a reaction product (polymer) in which two aromatic compounds (A) are linked to one carbon atom of the cyclic carbonyl compound (B) can be obtained.

[0084] As the acid catalyst used in the reaction, inorganic acids such as sulfuric acid, phosphoric acid, and perchloric acid, organic sulfonic acids such as p-toluenesulfonic acid, p-toluenesulfonic acid monohydrate, and methanesulfonic acid, and carboxylic acids such as formic acid and oxalic acid are used. The amount of the acid catalyst used is variously selected according to the type of acid used. Usually, it is 0.001 to 10000 parts by mass, preferably 0.01 to 1000 parts by mass, and more preferably 0.1 to 100 parts by mass, relative to 100 parts by mass of the aromatic compound (A).

[0085] The above condensation reaction and addition reaction can be carried out without a solvent, but are usually carried out using a solvent. As a solvent, any solvent can be used as long as it does not hinder the reaction. Examples include 1,2-dimethoxyethane, diethylene glycol dimethyl ether, propylene glycol monomethyl ether, tetrahydrofuran, dimethoxyethane ... Alkanes and other ethers.

[0086] The reaction temperature is usually 40° C. to 200° C. The reaction time is variously selected depending on the reaction temperature, but is usually about 30 minutes to 50 hours.

[0087] The weight average molecular weight Mw of the polymer obtained as described above is usually 500 to 1,000,000, or 600 to 500,000.

[0088] The reaction products that can be preferably used in the present invention will be described in the examples.

[0089] [Solvent]

[0090] As the solvent of the resist underlayer film forming composition according to the present invention, any solvent that can dissolve the reaction product can be used without particular limitation. In particular, since the resist underlayer film forming composition according to the present invention is used in a uniform solution state, it is recommended to use a solvent generally used in a photolithography process in combination in consideration of its coating performance.

[0091] Examples of such solvents include methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, methyl isobutyl carbinol, propylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexanone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxylate, ethyl hydroxylate, methyl 2-hydroxy-3-methylbutyrate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate. Ester, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol monomethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol dipropyl ether, propylene glycol dibutyl ether, ethyl lactate, propyl lactate, isopropyl lactate, butyl lactate, isopropyl lactate Butyl ester, methyl formate, ethyl formate, propyl formate, isopropyl formate, butyl formate, isobutyl formate, pentyl formate, isoamyl formate, methyl acetate, ethyl acetate, pentyl acetate, isoamyl acetate, hexyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, butyl propionate, isobutyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, ethyl hydroxyacetate, ethyl 2-hydroxy-2-methylpropionate, methyl 3-methoxy-2-methylpropionate, methyl 2-hydroxy-3-methylbutyrate, ethyl methoxyacetate, ethyl ethoxyacetate, 3-methyl The solvents include methyl 3-ethoxypropionate, ethyl 3-methoxypropionate, ethyl 3-methoxypropionate, 3-methoxybutyl acetate, 3-methoxypropyl acetate, 3-methyl-3-methoxybutyl acetate, 3-methyl-3-methoxybutyl propionate, 3-methyl-3-methoxybutyl butyrate, methyl acetoacetate, toluene, xylene, methyl ethyl ketone, methyl propyl ketone, methyl butyl ketone, 2-heptanone, 3-heptanone, 4-heptanone, cyclohexanone, N,N-dimethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpyrrolidone, 4-methyl-2-pentanol, and γ-butyrolactone. These solvents may be used alone or in combination of two or more.

[0092] Furthermore, the following compounds described in Japanese Patent Application No. 2017-140193 can also be used.

[0093]

[0094] (R in formula (i) 1 , R 2and R 3 Each represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms which may be interrupted by an oxygen atom, a sulfur atom or an amide bond, and may be the same or different from each other and may be bonded to each other to form a ring structure.

[0095] Examples of the alkyl group having 1 to 20 carbon atoms include linear or branched alkyl groups which may or may not have a substituent, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, n-octyl, cyclohexyl, 2-ethylhexyl, n-nonyl, isononyl, p-tert-butylcyclohexyl, n-decyl, n-dodecylnonyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and eicosyl. An alkyl group having 1 to 12 carbon atoms is preferred, an alkyl group having 1 to 8 carbon atoms is more preferred, and an alkyl group having 1 to 4 carbon atoms is further preferred.

[0096] Examples of the alkyl group having 1 to 20 carbon atoms interrupted by an oxygen atom, a sulfur atom or an amide bond include groups containing the structural unit -CH2-O-, -CH2-S-, -CH2-NHCO- or -CH2-CONH-. -O-, -S-, -NHCO- or -CONH- may have one unit or two or more units in the alkyl group. Specific examples of the alkyl group having 1 to 20 carbon atoms interrupted by -O-, -S-, -NHCO- or -CONH- units include methoxy, ethoxy, propoxy, butoxy, methylthio, ethylthio, propylthio, butylthio, methylcarbonylamino, ethylcarbonylamino, propylcarbonylamino, butylcarbonylamino, methylaminocarbonyl, ethylaminocarbonyl, propylaminocarbonyl, butylaminocarbonyl, and the like, and further include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, or octadecyl, and each of which is substituted by methoxy, ethoxy, propoxy, butoxy, methylthio, ethylthio, propylthio, butylthio, methylcarbonylamino, ethylcarbonylamino, methylaminocarbonyl, ethylaminocarbonyl, and the like. Preferred are methoxy, ethoxy, methylthio, and ethylthio, and more preferred are methoxy and ethoxy.

[0097] These solvents have relatively high boiling points and are therefore effective in imparting high embedding properties and high planarizing properties to the resist underlayer film-forming composition.

[0098] Specific examples of preferred compounds represented by formula (i) are shown below.

[0099]

[0100] Among the above, preferred are 3-methoxy-N,N-dimethylpropionamide, N,N-dimethylisobutylamide, and the compound represented by the following formula. As the compound represented by formula (i), 3-methoxy-N,N-dimethylpropionamide and N,N-dimethylisobutylamide are particularly preferred.

[0101]

[0102] These solvents can be used alone or in combination of two or more. Among these solvents, solvents having a boiling point of 160°C or above are preferred, and propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, butyl lactate, cyclohexanone, 3-methoxy-N,N-dimethylpropionamide, N,N-dimethylisobutylamide, 2,5-dimethylhexane-1,6-diyldiacetate (DAH; cas, 89182-68-3), and 1,6-diacetoxyhexane (cas, 6222-17-9) are preferred. Propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and N,N-dimethylisobutylamide are particularly preferred.

[0103] [Crosslinking agent component]

[0104] The resist underlayer film forming composition of the present invention may include a crosslinking agent component. As the crosslinking agent, melamine-based, substituted urea-based, or polymers thereof may be cited. Preferably, the crosslinking agent has at least two crosslinking substituents, such as methoxymethylated glycoluril, butoxymethylated glycoluril, methoxymethylated melamine, butoxymethylated melamine, methoxymethylated benzoguanamine, butoxymethylated benzoguanamine, methoxymethylated urea, butoxymethylated urea, or methoxymethylated thiourea. In addition, condensates of these compounds may also be used.

[0105] As the crosslinking agent, a crosslinking agent with high heat resistance can be used. As the crosslinking agent with high heat resistance, a compound containing a crosslinking-forming substituent having an aromatic ring (for example, a benzene ring or a naphthalene ring) in the molecule can be preferably used.

[0106] Examples of the compound include a compound having a partial structure of the following formula (4) and a polymer or oligomer having a repeating unit of the following formula (5).

[0107]

[0108] The above R 11 , R 12 , R 13 , and R 14 It is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and the alkyl groups exemplified above can be used.

[0109] The compounds, polymers and oligomers of formula (4) and formula (5) are exemplified below.

[0110]

[0111]

[0112] The above compounds can be obtained as products of Asahi Organic Materials Industries, Ltd. and Honshu Chemical Industries, Ltd. For example, among the above crosslinking agents, the compound of formula (4-24) can be obtained as TM-BIP-A from Asahi Organic Materials Industries, Ltd.

[0113] The amount of the crosslinking agent added varies depending on the coating solvent used, the base substrate used, the required solution viscosity, the required film shape, etc., but is 0.001 to 80% by mass, preferably 0.01 to 50% by mass, and more preferably 0.05 to 40% by mass relative to the total solid content. These crosslinking agents may also undergo a crosslinking reaction caused by self-condensation, but when there is a crosslinkable substituent in the above-mentioned reaction product of the present invention, a crosslinking reaction may occur with these crosslinkable substituents.

[0114] [Acid and / or acid generator]

[0115] The resist underlayer film-forming composition of the present invention may contain an acid and / or an acid generator.

[0116] Examples of the acid include p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridine p-Toluenesulfonate, salicylic acid, 5-sulfosalicylic acid, 4-phenolsulfonic acid, camphorsulfonic acid, 4-chlorobenzenesulfonic acid, benzenedisulfonic acid, 1-naphthalenesulfonic acid, citric acid, benzoic acid, hydroxybenzoic acid, naphthoic acid, etc.

[0117] The acid may be used alone or in combination of two or more thereof. The amount thereof added is usually 0.0001 to 20% by mass, preferably 0.0005 to 10% by mass, and more preferably 0.01 to 3% by mass, based on the total solid content.

[0118] Examples of the acid generator include a thermal acid generator and a photoacid generator.

[0119] Examples of the thermal acid generator include 2,4,4,6-tetrabromocyclohexadienone, benzoin toluenesulfonate, 2-nitrobenzyl toluenesulfonate, and other organic sulfonic acid alkyl esters.

[0120] The photoacid generator generates acid when the resist is exposed. Therefore, the acidity of the lower film can be adjusted. This is a method for making the acidity of the lower film compatible with the acidity of the upper resist. In addition, by adjusting the acidity of the lower film, the pattern shape of the resist formed on the upper layer can be adjusted.

[0121] Examples of the photoacid generator contained in the resist underlayer film-forming composition of the present invention include: Salt compounds, sulfonimide compounds, and disulfonyldiazomethane compounds, etc.

[0122] As Salt compounds, such as diphenyl iodide Hexafluorophosphate, diphenyl iodide Trifluoromethanesulfonate, diphenyl iodide Nonafluorobutane sulfonate, diphenyl iodide Perfluorooctane sulfonate, diphenyl iodide Camphorsulfonate, bis(4-tert-butylphenyl)iodide Camphorsulfonate and bis(4-tert-butylphenyl)iodide Trifluoromethanesulfonate and other iodine Sulfonium salt compounds, and sulfonium salt compounds such as triphenylsulfonium hexafluoroantimonate, triphenylsulfonium nonafluoro-n-butanesulfonate, triphenylsulfonium camphorsulfonate and triphenylsulfonium trifluoromethanesulfonate.

[0123] Examples of the sulfonyl imide compound include N-(trifluoromethanesulfonyloxy)succinimide, N-(nonafluoro-n-butanesulfonyloxy)succinimide, N-(camphorsulfonyloxy)succinimide, and N-(trifluoromethanesulfonyloxy)naphthalimide.

[0124] Examples of the disulfonyldiazomethane compound include bis(trifluoromethylsulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(phenylsulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, bis(2,4-dimethylbenzenesulfonyl)diazomethane, and methylsulfonyl-p-toluenesulfonyldiazomethane.

[0125] The acid generator may be used alone or in combination of two or more.

[0126] When the acid generator is used, the ratio thereof is 0.01 to 5 parts by mass, or 0.1 to 3 parts by mass, or 0.5 to 1 part by mass based on 100 parts by mass of the solid content of the resist underlayer film-forming composition.

[0127] [Other ingredients]

[0128] The resist underlayer film-forming composition of the present invention may contain a surfactant in order to prevent the occurrence of pinholes, streaks, etc. and to further improve the coating properties on uneven surfaces. Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether, polyoxyethylene alkyl allyl ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether, polyoxyethylene / polyoxypropylene block copolymers, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate, and sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate. Nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters such as tristearate, Eftop EF301, EF303, EF352 (trade names of Tokem Projects), Megaphac F171, F173, R-40, R-40N, R-40LM (trade names of DIC Corporation), Fluorade FC430 , FC431 (Sumitomo Slide (Co., Ltd., trade name), Asahigard AG710, Surflon S-382, SC101, SC102, SC103, SC104, SC105, SC106 (Asahi Glass (Co., Ltd., trade name) and other fluorine-based surfactants, organosiloxane polymer KP341 (Shin-Etsu Chemical Co., Ltd.), etc. The amount of these surfactants is usually 2.0% by mass or less, preferably 1.0% by mass or less, relative to the total solid content of the resist underlayer film material. These surfactants can be used alone or in combination of two or more. When using a surfactant, its ratio is 0.0001 to 5 parts by mass, or 0.001 to 1 part by mass, or 0.01 to 0.5 parts by mass relative to 100 parts by mass of the solid content of the resist underlayer film forming composition.

[0129] The resist underlayer film-forming composition of the present invention may be added with a light absorber, a rheology modifier, an adhesion promoter, etc. The rheology modifier is effective in improving the fluidity of the underlayer film-forming composition. The adhesion promoter is effective in improving the adhesion between the semiconductor substrate or the resist and the underlayer film.

[0130] As the light absorber, for example, commercially available light absorbers described in "Technology and Market of Industrial Pigments" (published by CMC) and "Dye Handbook" (edited by the Society of Synthetic Organic Chemistry) can be suitably used, for example, CI Disperse Yellow 1, 3, 4, 5, 7, 8, 13, 23, 31, 49, 50, 51, 54, 60, 64, 66, 68, 79, 82, 88, 90, 93, 102, 114 and 124; CI Disperse Orange 1, 5, 13, 25, 29, 30, CI Disperse Red 1, 5, 7, 13, 17, 19, 43, 50, 54, 58, 65, 72, 73, 88, 117, 137, 143, 199 and 210; CI Disperse Violet 43; CI Disperse Blue 96; CI Fluorescent Brighteners 112, 135 and 163; CI Solvent Orange 2 and 45; CI Solvent Red 1, 3, 8, 23, 24, 25, 27 and 49; CI Pigment Green 10; CI Pigment Brown 2, etc. The light absorber is usually blended in a ratio of 10% by mass or less, preferably 5% by mass or less, based on the total solid content of the resist underlayer film-forming composition.

[0131] The rheology modifier mainly improves the fluidity of the resist underlayer film forming composition, and is added for the purpose of improving the film thickness uniformity of the resist underlayer film and improving the filling property of the resist underlayer film forming composition into the inside of the hole, particularly in the baking process. As specific examples, phthalic acid derivatives such as dimethyl phthalate, diethyl phthalate, diisobutyl phthalate, dihexyl phthalate, butyl isodecyl phthalate, adipic acid derivatives such as di-n-butyl adipate, diisobutyl adipate, diisooctyl adipate, octyldecyl adipate, maleic acid derivatives such as di-n-butyl maleate, diethyl maleate, dinonyl maleate, oleic acid derivatives such as methyl oleate, butyl oleate, tetrahydrofurfuryl oleate, or stearic acid derivatives such as n-butyl stearate and glyceryl stearate can be cited. These rheology control agents are usually blended in a ratio of less than 30% by mass based on the total solid content of the resist underlayer film-forming composition.

[0132] The adhesion aid is mainly added for the purpose of improving the adhesion between the substrate or the resist and the resist underlayer film-forming composition, and in particular, for the purpose of preventing the resist from peeling off during development. Specific examples include chlorosilanes such as trimethylchlorosilane, dimethylhydroxymethylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylhydroxymethylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole; silanes such as hydroxymethyltrichlorosilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane; benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and 2-mercaptobenzothiazole. Heterocyclic compounds such as azole, urea, thiouracil, mercaptoimidazole, and mercaptopyrimidine, ureas such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. These adhesion promoters are usually blended in a ratio of less than 5% by mass, preferably less than 2% by mass, relative to the total solid content of the resist underlayer film forming composition.

[0133] The solid content of the resist underlayer film forming composition of the present invention is usually 0.1 to 70% by mass, preferably 0.1 to 60% by mass. The solid content is the content ratio of all components after removing the solvent from the resist underlayer film forming composition. The ratio of the above-mentioned reaction product in the solid content is preferably in the order of 1 to 100% by mass, 1 to 99.9% by mass, 50 to 99.9% by mass, 50 to 95% by mass, and 50 to 90% by mass.

[0134] One of the criteria for evaluating whether the resist underlayer film forming composition is in a uniform solution state is to observe the passability through a specific microfilter. The resist underlayer film forming composition according to the present invention is in a uniform solution state when passing through a microfilter with a pore size of 0.1 μm.

[0135] As the material of the above-mentioned microfilter, fluororesins such as PTFE (polytetrafluoroethylene), PFA (tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer), PE (polyethylene), UPE (ultra-high molecular weight polyethylene), PP (polypropylene), PSF (polysulfone), PES (polyethersulfone), and nylon can be cited, and PTFE (polytetrafluoroethylene) is preferred.

[0136] [Resist underlayer film and method for manufacturing semiconductor device]

[0137] Hereinafter, a method for producing a resist underlayer film and a semiconductor device using the resist underlayer film-forming composition according to the present invention will be described.

[0138] On a substrate used in the manufacture of a semiconductor device (for example, a silicon wafer substrate, a silicon / silicon dioxide coated substrate, a silicon nitride substrate, a glass substrate, an ITO substrate, a polyimide substrate, and a low dielectric constant material (low-k material) coated substrate, etc.), the resist underlayer film forming composition of the present invention is applied by an appropriate coating method such as a spin coater or a coater, and then fired to form a resist underlayer film. As firing conditions, a firing temperature of 80°C to 250°C and a firing time of 0.3 to 60 minutes are appropriately selected. Preferably, the firing temperature is 150°C to 250°C and the firing time is 0.5 to 2 minutes. Here, the film thickness of the formed underlayer film is, for example, 10 to 1000nm, or 20 to 500nm, or 30 to 300nm, or 50 to 200nm.

[0139] In addition, an inorganic resist underlayer film (hard mask) can also be formed on the organic resist underlayer film of the present invention. For example, in addition to the method of forming the resist underlayer film (inorganic resist underlayer film) containing silicon by spin coating with a composition described in WO2009 / 104552A1, an inorganic material film of Si can also be formed by CVD method etc.

[0140] In addition, by applying the composition for forming an anti-etching underlayer film according to the present invention onto a semiconductor substrate having a portion with a height difference and a portion without a height difference (a so-called height difference substrate), and firing the substrate, a resist underlayer film can be formed in which the height difference between the portion with the height difference and the portion without the height difference is in the range of 3 to 50 nm.

[0141] Next, a resist film, for example, a photoresist layer is formed on the resist underlayer film. The photoresist layer can be formed by a known method, that is, coating a photoresist composition solution on the underlayer film and firing. The film thickness of the photoresist is, for example, 50 to 10,000 nm, or 100 to 2,000 nm, or 200 to 1,000 nm.

[0142] The photoresist formed on the resist lower film is not particularly limited as long as it is a photoresist that is sensitive to the light used for exposure. Both negative photoresists and positive photoresists can be used. There are: positive photoresists composed of novolac resin and 1,2-naphthoquinone diazosulfonic acid ester, chemically amplified photoresists composed of a binder having a group that increases the alkali dissolution rate by acid decomposition and a photoacid generator, chemically amplified photoresists composed of a low molecular compound that increases the alkali dissolution rate of the photoresist by acid decomposition, an alkali-soluble binder, and a photoacid generator, and chemically amplified photoresists composed of a binder having a group that increases the alkali dissolution rate by acid decomposition, a low molecular compound that increases the alkali dissolution rate of the photoresist by acid decomposition, and a photoacid generator, etc. Examples include APEX-E manufactured by Shiplay Co., Ltd., PAR710 manufactured by Sumitomo Chemical Co., Ltd., and SEPR430 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, examples include fluorine-atom-containing polymer photoresists such as those described in Proc. SPIE, Vol. 3999, 330-334 (2000), Proc. SPIE, Vol. 3999, 357-364 (2000), and Proc. SPIE, Vol. 3999, 365-374 (2000).

[0143] Next, a resist pattern is formed by irradiation and development with light or electron beams. First, exposure is performed through a prescribed mask. Exposure uses near ultraviolet light, far ultraviolet light, or extreme ultraviolet light (for example, EUV (wavelength 13.5nm)). Specifically, KrF excimer laser (wavelength 248nm), ArF excimer laser (wavelength 193nm) and F2 excimer laser (wavelength 157nm) can be used. Among them, ArF excimer laser (wavelength 193nm) and EUV (wavelength 13.5nm) are preferred. After exposure, post-exposure baking can also be performed as needed. Post-exposure baking is performed under conditions appropriately selected from a heating temperature of 70°C to 150°C and a heating time of 0.3 to 10 minutes.

[0144] In addition, in the present invention, as a resist, a resist for electron beam lithography can be used instead of a photoresist. As an electron beam resist, both negative and positive types can be used. There are: a chemically amplified resist composed of an acid generator and an adhesive having a group that changes the alkali dissolution rate by acid decomposition, a chemically amplified resist composed of an alkali-soluble adhesive, an acid generator, and a low molecular compound that changes the alkali dissolution rate of the resist by acid decomposition, a chemically amplified resist composed of an acid generator and an adhesive having a group that changes the alkali dissolution rate by acid decomposition, and a low molecular compound that changes the alkali dissolution rate of the resist by acid decomposition, a non-chemically amplified resist composed of an adhesive having a group that changes the alkali dissolution rate by electron beam decomposition, a non-chemically amplified resist composed of an adhesive having a portion that changes the alkali dissolution rate by being cut by electron beam, etc. When these electron beam resists are used, a resist pattern can be formed in the same manner as when a photoresist is used by using electron beams as the irradiation source.

[0145] Next, development is performed using a developer. Thus, when a positive photoresist is used, for example, the photoresist in the exposed portion is removed, thereby forming a photoresist pattern.

[0146] As the developer, there can be cited as examples an aqueous solution of an alkali metal hydroxide such as potassium hydroxide or sodium hydroxide, an aqueous solution of a quaternary ammonium hydroxide such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, or choline, an aqueous solution of an amine such as ethanolamine, propylamine, or ethylenediamine. Furthermore, a surfactant or the like can be added to these developers. The conditions for development can be appropriately selected from a temperature of 5 to 50° C. and a time of 10 to 600 seconds.

[0147] Furthermore, the inorganic lower film (middle layer) is removed using the pattern of the photoresist (upper layer) formed in this way as a protective film, and then the organic lower film (lower layer) is removed using the film composed of the patterned photoresist and the inorganic lower film (middle layer) as a protective film. Finally, the semiconductor substrate is processed using the patterned inorganic lower film (middle layer) and the organic lower film (lower layer) as protective films.

[0148] First, the inorganic lower film (intermediate layer) of the portion where the photoresist is removed is removed by dry etching to expose the semiconductor substrate. The dry etching of the inorganic lower film can use tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, sulfur hexafluoride, difluoromethane, nitrogen trifluoride and chlorine trifluoride, chlorine, trichloroborane and dichloroborane and other gases. The dry etching of the inorganic lower film preferably uses a halogen-based gas, and more preferably a fluorine-based gas. As a fluorine-based gas, for example, tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane and difluoromethane (CH2F2) etc. can be cited.

[0149] Then, the organic lower film is removed using a film composed of the patterned photoresist and the inorganic lower film as a protective film. The organic lower film (lower layer) is preferably removed by dry etching using an oxygen-based gas. The reason is that the inorganic lower film containing a large amount of silicon atoms is not easily removed by dry etching using an oxygen-based gas.

[0150] Finally, the semiconductor substrate is processed. The semiconductor substrate is preferably processed by dry etching using a fluorine-based gas.

[0151] Examples of the fluorine-based gas include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).

[0152] In addition, an organic anti-reflection film can be formed on the upper layer of the resist underlayer film before the formation of the photoresist. The anti-reflection film composition used here is not particularly limited and can be arbitrarily selected from the materials conventionally used in the photolithography process so far and used. In addition, the anti-reflection film can be formed by conventional methods, for example, by coating and firing using a spin coater or a coating machine.

[0153] In the present invention, after forming an organic lower film on a substrate, an inorganic lower film can be formed thereon, and a photoresist can be further coated thereon. Thus, even when the pattern width of the photoresist becomes narrow and the photoresist is thinly coated to prevent the pattern from collapsing, the substrate can be processed by selecting an appropriate etching gas. For example, a fluorine-based gas having a sufficiently fast etching rate relative to the photoresist can be used as an etching gas to process the resist lower film, and a fluorine-based gas having a sufficiently fast etching rate relative to the inorganic lower film can be used as an etching gas to process the substrate, and an oxygen-based gas having a sufficiently fast etching rate relative to the organic lower film can be used as an etching gas to process the substrate.

[0154] The resist underlayer film formed by the resist underlayer film forming composition sometimes has absorption of the light according to the wavelength of the light used in the photolithography process. Moreover, in such a case, it can act as an anti-reflection film having the effect of preventing reflected light from the substrate. Further, the underlayer film formed by the resist underlayer film forming composition of the present invention can also act as a hard mask. The underlayer film of the present invention can also be used as a layer for preventing the interaction between the substrate and the photoresist, a layer having the function of preventing the material used in the photoresist or the material generated when the photoresist is exposed to the substrate from having adverse effects on the substrate, a layer having the function of preventing the material generated from the substrate during heating and firing from diffusing to the upper photoresist, and a barrier layer for reducing the poisoning effect of the photoresist layer caused by the semiconductor substrate dielectric layer, etc.

[0155] In addition, the underlayer film formed by the resist underlayer film forming composition can be applied to a substrate having a through hole formed therein used in a dual damascene process as an embedding material that can fill the hole without a gap. In addition, it can also be used as a planarizing material for planarizing the surface of a semiconductor substrate having uneven surfaces.

[0156] Example

[0157] The present invention will be described in further detail below with reference to Examples etc., but the present invention is not limited to the following Examples etc. at all.

[0158] The apparatus and the like used for measuring the weight average molecular weight of the polymer obtained in the following synthesis example are shown.

[0159] Device: HLC-8320GPC manufactured by Higashikata Co., Ltd.

[0160] GPC column: Shodex〔registered trademark〕Asahipak〔registered trademark〕(Showa Denko K.K.)

[0161] Column temperature: 40°C

[0162] Flow rate: 0.6mL / min

[0163] Eluent: N,N-dimethylformamide (DMF)

[0164] Standard sample: Polystyrene (Tosoh Corporation)

[0165] <Synthesis example 1>

[0166] In a 100 mL two-necked flask, 5.94 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of TEP-TPA (α,α,α',α'-tetrakis(4-hydroxyphenyl)-p-xylene, α,α,α',α'-tetrakis(4-hydroxyphenyl)-p-xylene, manufactured by Asahi Organic Materials Co., Ltd.), 15.07 g of propylene glycol monomethyl ether, 2.13 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.18 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 16 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate was filtered by suction, and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer corresponds to formula (2-1). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 96,600.

[0167]

[0168] <Synthesis example 2>

[0169] In a 100 mL two-necked flask, 9.57 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 3.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 16.00 g of propylene glycol monomethyl ether, 3.43 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.89 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 36 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-2). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 3,300.

[0170]

[0171] <Synthesis example 3>

[0172] In a 100 mL two-necked flask, 10.42 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.00 g of 2-phenylindole (manufactured by Tokyo Chemical Industry Co., Ltd.), 19.14 g of propylene glycol monomethyl ether, 3.73 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.06 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 15 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-3). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,250.

[0173]

[0174] <Synthesis example 4>

[0175] In a 100 mL two-necked flask, 12.84 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of N-phenyl-1-naphthylamine (manufactured by Tokyo Chemical Industry Co., Ltd.), 24.44 g of propylene glycol monomethyl ether, 4.60 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.54 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 15 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-4). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,260.

[0176]

[0177] <Synthesis example 5>

[0178] In a 100 mL two-necked flask, 8.04 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of 9,9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 17.92 g of propylene glycol monomethyl ether, 2.88 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.59 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 26 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-5). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,000.

[0179]

[0180] <Synthesis example 6>

[0181] In a 100 mL two-necked flask, 12.57 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.00 g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 22.07 g of propylene glycol monomethyl ether, 4.50 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.49 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 15 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-6). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,690.

[0182]

[0183] <Synthesis Example 7>

[0184] In a 100 mL two-necked flask, 12.04 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 21.35 g of propylene glycol monomethyl ether, 4.31 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.38 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 15 hours. After the reaction was completed, the solution was added dropwise to a methanol solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-7). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 4,000.

[0185]

[0186] <Synthesis example 8>

[0187] In a 100 mL two-necked flask, 5.09 g of cortisone acetate (manufactured by Tokyo Chemical Industry Co., Ltd.), 6.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 12.31 g of propylene glycol monomethyl ether, 1.22 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.67 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 16 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-8). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 4,000.

[0188]

[0189] <Synthesis Example 9>

[0190] In a 100 mL two-necked flask, 2.25 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 6.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 9.47 g of propylene glycol monomethyl ether, 1.22 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.67 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 16 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-9). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 347,200.

[0191]

[0192] <Synthesis Example 10>

[0193] In a 100 mL two-necked flask, 8.47 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 6.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 16.00 g of propylene glycol monomethyl ether, 4.57 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.52 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 36 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-10). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 3,300.

[0194]

[0195] <Synthesis Example 11>

[0196] In a 100 mL two-necked flask, 8.29 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 9.00 g of 2-phenylindole (manufactured by Tokyo Chemical Industry Co., Ltd.), 21.77 g of propylene glycol monomethyl ether, 4.48 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.47 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and stirred under reflux for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-11). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,600.

[0197]

[0198] <Synthesis Example 12>

[0199] In a 100 mL two-necked flask, 7.31 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 9.00 g of N-phenyl-1-naphthylamine (manufactured by Tokyo Chemical Industry Co., Ltd.), 20.25 g of propylene glycol monomethyl ether, 3.94 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.18 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-12). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 4,100.

[0200]

[0201] <Synthesis Example 13>

[0202] In a 100 mL two-necked flask, 4.57 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 9.00 g of 9,9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 16.04 g of propylene glycol monomethyl ether, 2.47 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.36 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and stirred under reflux for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-13). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 3,000.

[0203]

[0204] <Synthesis Example 14>

[0205] In a 100 mL two-necked flask, add 7.78 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 18.98 g of propylene glycol monomethyl ether, 4.20 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.32 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 21 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-14). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 2,050.

[0206]

[0207] <Synthesis Example 15>

[0208] In a 100 mL two-necked flask, add 8.53 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 8.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 21.13 g of propylene glycol monomethyl ether, 4.60 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.54 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 10 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-15). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 3,300.

[0209]

[0210] <Synthesis Example 16>

[0211] In a 100 mL two-necked flask, 4.89 g of (+)-10-camphorsulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 16.92 g of propylene glycol monomethyl ether, 2.03 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.12 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 15 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-16). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 18,700.

[0212]

[0213] <Synthesis Example 17>

[0214] In a 100 mL two-necked flask, add 9.20 g of (+)-10-camphorsulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 18.01 g of propylene glycol monomethyl ether, 3.81 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.10 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 10 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-17). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 2,400.

[0215]

[0216] <Synthesis Example 18>

[0217] In a 100 mL two-necked flask, 4.08 g of D-glucuronic acid-6,3-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 11.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 17.31 g of propylene glycol monomethyl ether, 2.23 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.23 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 10 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-18). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 6,700.

[0218]

[0219] <Synthesis Example 19>

[0220] In a 100 mL two-necked flask, add 4.08 g of D-arabinose ascorbic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 11.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 17.31 g of propylene glycol monomethyl ether, 2.23 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.23 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 16 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-19). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 12,600.

[0221]

[0222] <Synthesis Example 20>

[0223] In a 100 mL two-necked flask, 9.07 g of D-arabinose ascorbic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 6.50 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 20.53 g of propylene glycol monomethyl ether, 4.95 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 2.74 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 0.5 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-20). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,740.

[0224]

[0225] <Synthesis Example 21>

[0226] In a 100 mL two-necked flask, 5.29 g of DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemicals Co., Ltd.), 12.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 16.75 g of propylene glycol monomethyl ether, 4.19 g of N-methylpyrrolidone, 3.65 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 2.01 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 43 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-21).

[0227] The weight average molecular weight Mw measured by GPC in terms of polystyrene was 9,050.

[0228]

[0229] <Synthesis Example 22>

[0230] In a 100 mL two-necked flask, add 4.28 g of MA-ICA (monoallyl isocyanurate, manufactured by Shikoku Chemicals Co., Ltd.), 12.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 14.97 g of propylene glycol monomethyl ether, 3.74 g of N-methylpyrrolidone, 2.43 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 1.34 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 43 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution and reprecipitated. The resulting precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. The resulting polymer is equivalent to formula (2-22).

[0231] The weight average molecular weight Mw measured by GPC in terms of polystyrene was 3,500.

[0232]

[0233] <Synthesis Example 23>

[0234] In a 100 mL two-necked flask, 4.68 g of MB-ICA (mono-n-butyl isocyanurate, manufactured by Kobe Natural Chemicals Co., Ltd.), 12.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 16.27 g of propylene glycol monomethyl ether, 4.07 g of N-methylpyrrolidone, 3.65 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 2.01 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 43 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-23).

[0235] The weight average molecular weight Mw measured by GPC in terms of polystyrene was 22,100.

[0236]

[0237] <Synthesis Example 24>

[0238] In a 100 mL two-necked flask, 11.61 g of DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.), 7.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 21.29 g of propylene glycol monomethyl ether, 5.32 g of N-methylpyrrolidone, 4.19 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), 8.00 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 4.42 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and stirred under reflux for about 100 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-24). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,090.

[0239]

[0240] <Synthesis Example 25>

[0241] In a 100 mL two-necked flask, DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.) 8.66 g, 2-phenylindole (manufactured by Tokyo Chemical Industry Co., Ltd.) 8.00 g, propylene glycol monomethyl ether 18.10 g, N-methylpyrrolidone 4.53 g, methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.) 5.97 g, methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) 3.30 g, and 3-mercaptopropionic acid 2.06 g were added. Then, heating was performed until 140°C, and reflux stirring was performed for about 59 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered, and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-25). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,000.

[0242]

[0243] <Synthesis Example 26>

[0244] In a 100 mL two-necked flask, DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.) 8.59 g, N-phenyl-1-naphthylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) 9.00 g, propylene glycol monomethyl ether 18.80 g, N-methylpyrrolidone 4.70 g, methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.) 4.19 g, methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) 5.97 g, and 3-mercaptopropionic acid 3.27 g were added. Then, heating was performed until 140°C and refluxed with stirring for about 59 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-26). The weight average molecular weight Mw measured by GPC in terms of polystyrene conversion is 770.

[0245]

[0246] <Synthesis Example 27>

[0247] In a 100 mL two-necked flask, 5.97 g of DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.), 10.00 g of 9,9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 16.07 g of propylene glycol monomethyl ether, 4.02 g of N-methylpyrrolidone, 4.11 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 2.27 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and stirred under reflux for about 59 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-27). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,780.

[0248]

[0249] <Synthesis Example 28>

[0250] In a 100 mL two-necked flask, 10.45 g of DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.), 8.00 g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 20.52 g of propylene glycol monomethyl ether, 5.13 g of N-methylpyrrolidone, 7.20 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 3.98 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 140°C and refluxed with stirring for about 59 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-28). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,300.

[0251]

[0252] <Synthesis Example 29>

[0253] In a 100 mL two-necked flask, add DA-ICA (diallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.) 8.76 g, carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.) 7.00 g, propylene glycol monomethyl ether 17.44 g, N-methylpyrrolidone 4.36 g, methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.) 6.04 g, and 3-mercaptopropionic acid 3.34 g. Then heat to 150°C and reflux with stirring for about 44 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution for reprecipitation. The resulting precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the resulting polymer is equivalent to formula (2-29). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 4,700.

[0254]

[0255] <Synthesis Example 30>

[0256] In a 100 mL two-necked flask, add 8.09 g of MA-ICA (monoallyl isocyanurate, manufactured by Shikoku Chemical Industry Co., Ltd.), 8.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 16.55 g of propylene glycol monomethyl ether, 4.14 g of N-methylpyrrolidone, 4.60 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 2.54 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 44 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-30). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 3,100.

[0257]

[0258] <Synthesis Example 31>

[0259] In a 100 mL two-necked flask, add 8.85 g of MB-ICA (mono-n-butyl isocyanurate, manufactured by Kobe Natural Chemicals Co., Ltd.), 8.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 19.00 g of propylene glycol monomethyl ether, 4.75 g of N-methylpyrrolidone, 6.90 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 3.81 g of 3-mercaptopropionic acid. Then heat to 140°C and reflux with stirring for about 44 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution for reprecipitation. The resulting precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the resulting polymer is equivalent to formula (2-31). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 4,900.

[0260]

[0261] <Synthesis Example 32>

[0262] In a 100 mL two-necked flask, 12.00 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.49 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.22 g of 9,9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 22.47 g of propylene glycol monomethyl ether acetate, 0.86 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 1.90 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and stirred under reflux for about 12 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-32). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,200.

[0263]

[0264] <Synthesis Example 33>

[0265] In a 100 mL two-necked flask, 8.42 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 4.38 g of DA-ICA (manufactured by Shikoku Chemical Industry Co., Ltd.), 7.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 24.39 g of propylene glycol monomethyl ether, 6.10 g of N-methylpyrrolidone, 4.02 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 6.67 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-33). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,000.

[0266]

[0267] <Synthesis Example 34>

[0268] In a 100 mL two-necked flask, add 9.02 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.50 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 4.00 g of D-(+)-glucono-1,5-lactone (manufactured by Tokyo Chemical Industry Co., Ltd.), 24.67 g of propylene glycol monomethyl ether, 1.29 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 2.86 g of 3-mercaptopropionic acid. Then heat to 150°C and reflux with stirring for about 12 hours. After the reaction is completed, the solution is added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate is filtered and the filtrate is dried under reduced pressure at 60°C overnight. In this way, the obtained polymer is equivalent to formula (2-34). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,200.

[0269]

[0270] <Synthesis Example 35>

[0271] In a 100 mL two-necked flask, 9.58 g of dehydrocholic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 6.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 3.72 g of 1-naphthaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 23.69 g of propylene glycol monomethyl ether, 1.37 g of methanesulfonic acid (manufactured by Kanto Chemical Co., Ltd.), and 3.03 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 16 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. In this way, the obtained polymer was equivalent to formula (2-35). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,300.

[0272]

[0273] <Comparative Synthesis Example 1>

[0274] In a 100 mL two-necked flask, 4.48 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of TEP-TPA (manufactured by Asahi Organic Materials Co., Ltd.), 35.67 g of propylene glycol monomethyl ether, and 0.91 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 4 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-1). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 195,900.

[0275]

[0276] <Comparative Synthesis Example 2>

[0277] In a 100 mL two-necked flask, 8.41 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 43.86 g of propylene glycol monomethyl ether, and 0.38 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 4 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-2). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 8,100.

[0278]

[0279] <Comparative Synthesis Example 3>

[0280] In a 100 mL two-necked flask, 5.49 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of 2-phenylindole (manufactured by Tokyo Chemical Industry Co., Ltd.), 16.49 g of propylene glycol monomethyl ether acetate, and 0.99 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 5 hours. After the reaction was completed, the solution was added dropwise to methanol for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-3). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,600.

[0281]

[0282] <Comparative Synthesis Example 4>

[0283] In a 100 mL two-necked flask, 4.84 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of N-phenyl-1-naphthylamine (manufactured by Tokyo Chemical Industry Co., Ltd.), 36.67 g of propylene glycol monomethyl ether acetate, and 0.88 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 15 minutes. After the reaction was completed, the solution was added dropwise to methanol and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-4). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 5,900.

[0284]

[0285] <Comparative Synthesis Example 5>

[0286] In a 100 mL two-necked flask, 3.03 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of 9,9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 32.68 g of propylene glycol monomethyl ether acetate, and 0.55 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 17.5 hours. After the reaction was completed, the solution was added dropwise to methanol and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-5). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 910,300.

[0287]

[0288] <Comparative Synthesis Example 6>

[0289] In a 100 mL two-necked flask, 6.62 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 41.58 g of propylene glycol monomethyl ether acetate, and 1.20 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 1.5 hours. After the reaction was completed, the solution was added dropwise to methanol and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-6). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 5,300.

[0290]

[0291] <Comparative Synthesis Example 7>

[0292] In a 100 mL two-necked flask, 6.35 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 40.84 g of propylene glycol monomethyl ether acetate, and 1.15 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 30 minutes. After the reaction was completed, the solution was added dropwise to methanol for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-7). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 52,300.

[0293]

[0294] <Example 1>

[0295] The resin obtained in Synthesis Example 1 (i.e., polymer, the same below) was dissolved in propylene glycol monomethyl ether, and then ion exchanged to obtain a resin solution (solid content 18.86% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.45 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.69 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0296] <Example 2>

[0297] The resin obtained in Synthesis Example 2 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 19.80% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.28 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.85 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0298] <Example 3>

[0299] The resin obtained in Synthesis Example 3 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.33% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.18 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.24 g of the resin solution. 1.34 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.48 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0300] <Example 4>

[0301] The resin obtained in Synthesis Example 4 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 19.84% by mass). To 3.00 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 1.34 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.73 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0302] <Example 5>

[0303] The resin obtained in Synthesis Example 5 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.64% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.49 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.65 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0304] <Example 6>

[0305] The resin obtained in Synthesis Example 6 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 17.66% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.57 g of the resin solution. 1.34 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.36 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0306] <Example 7>

[0307] The resin obtained in Synthesis Example 7 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 24.32% by mass). To 2.67 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 3.46 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0308] <Example 8>

[0309] The resin obtained in Synthesis Example 8 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.86% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.45 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.69 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0310] <Example 9>

[0311] The resin obtained in Synthesis Example 9 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 14.20% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.58 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.56 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0312] <Example 10>

[0313] The resin obtained in Synthesis Example 10 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 15.92% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.08 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.05 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0314] <Example 11>

[0315] The resin obtained in Synthesis Example 11 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 19.67% by mass). To 2.98 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.17 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 2.18 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.93 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0316] <Example 12>

[0317] The resin obtained in Synthesis Example 12 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 12.29 mass %). To 5.29 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 0.85 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0318] <Example 13>

[0319] The resin obtained in Synthesis Example 13 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 19.35% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.36 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.78 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0320] <Example 14>

[0321] The resin obtained in Synthesis Example 14 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.26% by mass). To 3.56 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.58 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0322] <Example 15>

[0323] The resin obtained in Synthesis Example 15 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.34% by mass). To 3.54 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.59 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0324] <Example 16>

[0325] The resin obtained in Synthesis Example 16 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.26% by mass). To 3.56 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.58 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0326] <Example 17>

[0327] The resin obtained in Synthesis Example 17 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 15.77% by mass). To 3.94 g of the resin solution, 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megafac R-40), 0.26 g of PGME-BIP-A (Fine Chem Co., Ltd.), 1.16 g of propylene glycol monomethyl ether containing 2% by mass of K-PURE [registered trademark] TAG2689 (King Instruments Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.98 g of propylene glycol monomethyl ether were added and dissolved, and filtered using a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0328] <Example 18>

[0329] The resin obtained in Synthesis Example 18 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.26% by mass). To 3.56 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 1.16 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.58 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0330] <Example 19>

[0331] The resin obtained in Synthesis Example 19 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.43% by mass). To 3.53 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.61 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0332] <Example 20>

[0333] The resin obtained in Synthesis Example 20 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 13.21% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of TMOM-BP (Honshu Chemical Industry Co., Ltd.), and 2% by mass of pyridine were added to 4.92 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-hydroxybenzenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.21 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0334] <Example 21>

[0335] The resin obtained in Synthesis Example 21 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 13.71% by mass). To 4.74 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.39 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0336] <Example 22>

[0337] The resin obtained in Synthesis Example 22 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 16.47% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.95 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.19 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0338] <Example 23>

[0339] The resin obtained in Synthesis Example 23 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 15.50% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.19 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.94 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0340] <Example 24>

[0341] The resin obtained in Synthesis Example 24 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 16.99% by mass). To 3.50 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 1.34 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.25 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0342] <Example 25>

[0343] The resin obtained in Synthesis Example 25 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 13.71% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.74 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.39 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0344] <Example 26>

[0345] The resin obtained in Synthesis Example 26 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 14.29% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.55 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.59 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0346] <Example 27>

[0347] The resin obtained in Synthesis Example 27 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 16.73% by mass). To 3.85 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.25 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0348] <Example 28>

[0349] The resin obtained in Synthesis Example 28 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 17.06% by mass). To 3.81 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.33 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0350] <Example 29>

[0351] The resin obtained in Synthesis Example 29 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.46% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.52 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.61 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0352] <Example 30>

[0353] The resin obtained in Synthesis Example 30 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 16.49% by mass). To 3.94 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.19 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0354] <Example 31>

[0355] The resin obtained in Synthesis Example 31 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 21.90% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 2.97 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 3.17 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0356] <Example 32>

[0357] The resin obtained in Synthesis Example 31 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 21.90% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 2.97 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.78 g of propylene glycol monomethyl ether acetate, 2.25 g of propylene glycol monomethyl ether and 1.84 g of N,N-dimethylisobutylamide were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0358] <Example 33>

[0359] The resin obtained in Synthesis Example 32 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 23.28% by mass). To 2.79 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.55 g of propylene glycol monomethyl ether acetate, and 5.48 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0360] <Example 34>

[0361] The resin obtained in Synthesis Example 33 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 19.84% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.28 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.86 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0362] <Example 35>

[0363] The resin obtained in Synthesis Example 34 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 21.71% by mass). To 2.99 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.35 g of propylene glycol monomethyl ether acetate, and 5.48 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0364] <Example 36>

[0365] The resin obtained in Synthesis Example 35 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 20.10% by mass). To 3.23 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 g of propylene glycol monomethyl ether acetate, and 5.48 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0366] <Comparative Example 1>

[0367] The resin obtained in Comparative Synthesis Example 1 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 15.22% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.27 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 1.86 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0368] <Comparative Example 2>

[0369] The resin obtained in Comparative Synthesis Example 2 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 16.80% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.87 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.27 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0370] <Comparative Example 3>

[0371] The resin obtained in Comparative Synthesis Example 3 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 22.51% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 2.89 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 4.14 g of propylene glycol monomethyl ether acetate, and 1.80 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0372] <Comparative Example 4>

[0373] The resin obtained in Comparative Synthesis Example 4 was dissolved in cyclohexanone and then subjected to ion exchange to obtain a resin solution (solid content: 17.72% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.67 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.86 g of propylene glycol monomethyl ether acetate, and 0.88 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0374] <Comparative Example 5>

[0375] The resin obtained in Comparative Synthesis Example 5 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 15.86% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 4.10 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.97 g of propylene glycol monomethyl ether acetate, and 1.80 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0376] <Comparative Example 6>

[0377] The resin obtained in Comparative Synthesis Example 6 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 18.21% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.57 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 2.70 g of propylene glycol monomethyl ether acetate, and 2.57 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0378] <Comparative Example 7>

[0379] The resin obtained in Comparative Synthesis Example 7 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 18.38% by mass). 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megaphage R-40), 0.13 g of PL-LI (Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added to 3.54 g of the resin solution. 0.97 g of propylene glycol monomethyl ether of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), 3.49 g of propylene glycol monomethyl ether acetate, and 1.80 g of propylene glycol monomethyl ether were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0380] [Dissolution test into resist solvent]

[0381] The solutions of the resist underlayer film-forming compositions prepared in Comparative Examples 1 to 7 and Examples 1 to 36 were applied to silicon wafers using a spin coater, and fired on a hot plate at 250° C. for 60 seconds to form resist underlayer films (film thickness 0.20 μm). These resist underlayer films were immersed in ethyl lactate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and cyclohexanone, which are solvents used for resists. These resist underlayer films are insoluble in these solvents.

[0382] [Measurement of optical constants]

[0383] The solutions of the resist underlayer film-forming compositions prepared in Comparative Examples 1 to 7 and Examples 1 to 36 were applied to silicon wafers using a spin coater. The resist underlayer films (film thickness 0.05 μm) were formed by firing at 250° C. on a hot plate for 60 seconds. The refractive index (n value) and optical absorption coefficient (also referred to as k value, attenuation coefficient) of these resist underlayer films were measured using a spectroscopic ellipsometer at a wavelength of 193 nm. The results are shown in Table 1.

[0384] [Table 1-1]

[0385] Table 1 Refractive index n and optical absorption coefficient k

[0386]

[0387] [Table 1-2]

[0388]

[0389] [Determination of dry etching rate]

[0390] The etcher and etching gas used for the measurement of the dry etching rate were as follows.

[0391] RIE-10NR (manufactured by SAMU): CF4

[0392] The solutions of the resist underlayer film-forming compositions prepared in Comparative Example 1-7 and Example 1-36 were applied to silicon wafers using a spin coater. The resist underlayer film (film thickness 0.20 μm) was formed by firing at 250° C. for 60 seconds on a hot plate. The dry etching rate was measured using CF4 gas as an etching gas, and the dry etching rates of the resist underlayer films of Comparative Example 1-7 and Example 1-36 were compared. The results are shown in Table 2. The dry etching rate ratio is the dry etching rate ratio of (resist underlayer film) / (KrF photoresist).

[0393] [Table 2-1]

[0394] Table 2 Dry etching speed ratio

[0395]

[0396] [Table 2-2]

[0397]

[0398] [Evaluation of embedding properties]

[0399] The embedding property was confirmed in the dense pattern area of ​​SiO2 substrate with a film thickness of 200nm, a groove width of 50nm and a spacing of 100nm. After the resist lower film forming composition modulated in Comparative Examples 1-3, 6, 7 and Embodiments 1-36 was coated on the above-mentioned substrate, it was sintered for 60 seconds at 250°C to form a resist lower film of about 200nm. The flattening property of the substrate was observed using a scanning electron microscope (S-4800) made by Hitachi HiTech Nologiz (Strain), and the presence or absence of the resist lower film forming composition filling into the pattern was confirmed (Table 3). ○ indicates good, and × indicates bad.

[0400] [Table 3-1]

[0401] Table 3 Evaluation of embedding performance

[0402]

[0403] [Table 3-2]

[0404]

[0405] <Synthesis Example 51>

[0406] Add tricyclic [5.2.1.0 2,6 ] 15.96 g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of phenol (manufactured by Tokyo Chemical Industry Co., Ltd.), 22.76 g of propylene glycol monomethyl ether acetate, 10.92 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 16.93 g of 3-mercaptopropionic acid. Then, it was heated to 140°C and refluxed with stirring for about 23 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-51). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,000.

[0407]

[0408] <Synthesis Example 52>

[0409] Add tricyclic [5.2.1.0 2,6]6.29g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 28.25g of propylene glycol monomethyl ether acetate, 1.21g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.67g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 17 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-52). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 2,400.

[0410]

[0411] <Synthesis Example 53>

[0412] In a 100 mL two-necked flask, 7.13 g of dicyclohexane-4,4'-dione monoethylene glycol acetal (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 20.20 g of propylene glycol monomethyl ether acetate, 0.86 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.48 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 2 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-53). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,300.

[0413]

[0414] <Synthesis Example 54>

[0415] In a 100 mL two-necked flask, 6.54 g of 1,4-cyclohexanedione monoethylene glycol acetal (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 23.12 g of propylene glycol monomethyl ether acetate, 1.21 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.67 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 17 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-54). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,200.

[0416]

[0417] <Synthesis Example 55>

[0418] In a 100 mL two-necked flask, 6.29 g of 2-adamantanone (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 22.75 g of propylene glycol monomethyl ether acetate, 1.21 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.67 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 17 hours. After the reaction was completed, the solution was added dropwise to a methanol solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer corresponds to formula (2-55). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 4,700.

[0419]

[0420] <Synthesis Example 56>

[0421] In a 100 mL two-necked flask, 6.46 g of cyclohexanone (manufactured by Tokyo Chemical Industry Co., Ltd.), 11.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 47.61 g of propylene glycol monomethyl ether acetate, 1.90 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.05 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 40 hours. After the reaction was completed, the solution was added dropwise to a methanol solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-56). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,800.

[0422]

[0423] <Synthesis Example 57>

[0424] In a 100 mL two-necked flask, 6.37 g of 2-cyclopentylcyclopentanone (manufactured by Tokyo Chemical Industry Co., Ltd.), 7.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 22.87 g of propylene glycol monomethyl ether acetate, 1.21 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.67 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 40 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-57). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,900.

[0425]

[0426] <Synthesis Example 58>

[0427] In a 100 mL two-necked flask, 6.47 g of 2-cyclohexylcyclohexanone (manufactured by Tokyo Chemical Industry Co., Ltd.), 6.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 21.12 g of propylene glycol monomethyl ether acetate, 1.04 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.57 g of 3-mercaptopropionic acid were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 40 hours. After the reaction was completed, the solution was added dropwise to a methanol solution for reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-58). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 6,200.

[0428]

[0429] <Synthesis Example 59>

[0430] Add tricyclic [5.2.1.0 2,6 ]4.49g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 4.67g of 1-naphthaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 24.69g of propylene glycol monomethyl ether acetate, 1.72g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 3.81g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 2.5 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-59). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,900.

[0431]

[0432] <Synthesis Example 60>

[0433] Add tricyclic [5.2.1.0 2,6 ]3.80g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 12.00g of TEP-TPA (manufactured by Tokyo Chemical Industry Co., Ltd.), 22.55g of propylene glycol monomethyl ether, 2.43g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 4.03g of 3-mercaptopropionic acid. Then, it was heated to 140°C and refluxed with stirring for about 12 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-60). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 2,500.

[0434]

[0435] <Synthesis Example 61>

[0436] In a 100 mL two-necked flask, 12.08 g of 2-cyclopentylcyclopentanone (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of phloroglucinol (manufactured by Tokyo Chemical Industry Co., Ltd.), 42.34 g of propylene glycol monomethyl ether, 7.63 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 12.63 g of 3-mercaptopropionic acid were added. Then, heating was performed until 140°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (2-61). The weight average molecular weight Mw measured by GPC in terms of polystyrene conversion is 600.

[0437]

[0438] <Synthesis Example 62>

[0439] Add tricyclic [5.2.1.0 2,6 ]6.99g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 9.00g of 2-phenylindole (manufactured by Tokyo Chemical Industry Co., Ltd.), 27.88g of propylene glycol monomethyl ether acetate, 4.48g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 7.42g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 12 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-62). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 600.

[0440]

[0441] <Synthesis Example 63>

[0442] Add tricyclic [5.2.1.0 2,6]6.16g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 9.00g of N-phenyl-1-naphthylamine (manufactured by Tokyo Chemical Industry Co., Ltd.), 25.44g of propylene glycol monomethyl ether acetate, 3.94g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 6.54g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-63). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,400.

[0443]

[0444] <Synthesis Example 64>

[0445] Add tricyclic [5.2.1.0 2,6 ]6.14g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 12.00g of 9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 19.22g of propylene glycol monomethyl ether acetate, 0.99g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.09g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 16 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-64). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 2,400.

[0446]

[0447] <Synthesis Example 65>

[0448] Add tricyclic [5.2.1.0 2,6 ]6.14g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 8.00g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 28.25g of propylene glycol monomethyl ether acetate, 4.80g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 7.95g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol / water solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-65). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,400.

[0449]

[0450] <Synthesis Example 66>

[0451] Add tricyclic [5.2.1.0 2,6 ]4.69g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 4.75g of 2-cyclopentylcyclopentanone (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.0g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 35.38g of propylene glycol monomethyl ether acetate, 6.00g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 9.94g of 3-mercaptopropionic acid. Then, it was heated to 150°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C for one night. The obtained polymer is equivalent to formula (2-66). The weight average molecular weight Mw measured by GPC in terms of polystyrene is 1,000.

[0452]

[0453] <Synthesis Example 67>

[0454] Add tricyclic [5.2.1.0 2,6 ] 7.00 g of decane-8-one (manufactured by Tokyo Chemical Industry Co., Ltd.), 3.73 g of 1,5-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.), 8.17 g of 9-bis(4-hydroxyphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd.), 30.81 g of propylene glycol monomethyl ether acetate, 4.48 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 7.42 g of 3-mercaptopropionic acid. Then, the mixture was heated to 150°C and refluxed with stirring for about 21 hours. After the reaction was completed, the solution was added dropwise to a methanol solution and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer corresponds to formula (2-67). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,700.

[0455]

[0456] <Comparative Synthesis Example 51>

[0457] In a 100 mL two-necked flask, 18.8 g of phenol (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.01 g of trifluoromethanesulfonic acid were added, and 8.00 g of dicyclopentadiene (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise while stirring at 50°C. After stirring at this temperature for 1 hour, the temperature was raised to 150°C and stirred for 2 hours to terminate the reaction. The unreacted product was removed by reprecipitation. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-51). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,000.

[0458]

[0459] <Comparative Synthesis Example 52>

[0460] In a 100 mL two-necked flask, 7.91 g of dicyclopentadiene (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 18.00 g of propylene glycol monomethyl ether acetate, and 0.09 g of trifluoromethanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. Then, the mixture was heated to 150°C and refluxed with stirring for about 12 hours. After the reaction was completed, the solution was added dropwise to methanol and reprecipitated. The obtained precipitate was filtered and the filtrate was dried under reduced pressure at 60°C overnight. The obtained polymer is equivalent to formula (1-52). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 3,000.

[0461]

[0462] <Example 51>

[0463] The resin obtained in Synthesis Example 51 (i.e., polymer, the same below) was dissolved in propylene glycol monomethyl ether acetate, and then ion exchange was performed to obtain a resin solution (solid content 21.57% by mass). To 3.27 g of the resin solution, 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine were added. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 1.01 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0464] <Example 52>

[0465] The resin obtained in Synthesis Example 52 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 19.86% by mass). To 2.53 g of the resin solution were added 0.05 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.13 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.63 g of propylene glycol monomethyl ether of benzenesulfonate, 0.69 g of propylene glycol monomethyl ether acetate, 0.31 g of propylene glycol monomethyl ether, and 3.68 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0466] <Example 53>

[0467] The resin obtained in Synthesis Example 53 was dissolved in cyclohexanone and then subjected to ion exchange to obtain a resin solution (solid content: 19.45% by mass). 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megafac R-40), 3.58 g of propylene glycol monomethyl ether acetate, 0.08 g of propylene glycol monomethyl ether, and 1.74 g of cyclohexanone were added to 3.51 g of the resin solution to dissolve the mixture, and the mixture was filtered using a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0468] <Example 54>

[0469] The resin obtained in Synthesis Example 54 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 23.34% by mass). 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (DIC Corporation, Megafac R-40), 3.57 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were added to 3.02 g of the resin solution to dissolve the mixture, and the mixture was filtered using a polytetrafluoroethylene microfilter having a diameter of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0470] <Example 55>

[0471] The resin obtained in Synthesis Example 55 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 21.53% by mass). To 2.62 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.14 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.71 g of propylene glycol monomethyl ether of benzenesulfonate, 0.80 g of propylene glycol monomethyl ether acetate, 0.04 g of propylene glycol monomethyl ether, and 3.64 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0472] <Example 56>

[0473] The resin obtained in Synthesis Example 56 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 17.65% by mass). To 3.20 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.14 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.71 g of propylene glycol monomethyl ether of benzenesulfonate, 0.22 g of propylene glycol monomethyl ether acetate, 0.04 g of propylene glycol monomethyl ether, and 3.64 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0474] <Example 57>

[0475] The resin obtained in Synthesis Example 57 was dissolved in cyclohexanone and then subjected to ion exchange to obtain a resin solution (solid content: 18.19% by mass). To 3.10 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.14 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.71 g of propylene glycol monomethyl ether of benzenesulfonate, 0.67 g of propylene glycol monomethyl ether acetate, 2.22 g of propylene glycol monomethyl ether, and 1.10 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0476] <Example 58>

[0477] The resin obtained in Synthesis Example 58 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 18.05% by mass). To 3.13 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.14 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.71 g of propylene glycol monomethyl ether of benzenesulfonate, 0.29 g of propylene glycol monomethyl ether acetate, 0.04 g of propylene glycol monomethyl ether, and 3.64 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0478] <Example 59>

[0479] The resin obtained in Synthesis Example 59 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 22.47% by mass). To 3.14 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 1.14 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0480] <Example 60>

[0481] The resin obtained in Synthesis Example 60 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 21.31% by mass). To 3.31 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 3.57 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0482] <Example 61>

[0483] The resin obtained in Synthesis Example 61 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 19.80% by mass). To 3.56 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 0.71 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0484] <Example 62>

[0485] The resin obtained in Synthesis Example 62 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 19.52% by mass). To 3.61 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 3.57 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0486] <Example 63>

[0487] The resin obtained in Synthesis Example 63 was dissolved in cyclohexanone and then subjected to ion exchange to obtain a resin solution (solid content: 18.98% by mass). To 3.30 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.16 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.78 g of propylene glycol monomethyl ether of benzenesulfonate, 0.86 g of propylene glycol monomethyl ether acetate, 0.15 g of propylene glycol monomethyl ether, and 4.68 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0488] <Example 64>

[0489] The resin obtained in Synthesis Example 64 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 19.00% by mass). To 3.46 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.16 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.82 g of propylene glycol monomethyl ether of benzenesulfonate, 0.79 g of propylene glycol monomethyl ether acetate, 0.11 g of propylene glycol monomethyl ether, and 4.58 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0490] <Example 65>

[0491] The resin obtained in Synthesis Example 65 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 20.75% by mass). To 3.40 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 3.57 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0492] <Example 66>

[0493] The resin obtained in Synthesis Example 66 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 23.14% by mass). To 3.05 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 3.57 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0494] <Example 67>

[0495] The resin obtained in Synthesis Example 67 was dissolved in propylene glycol monomethyl ether acetate and then subjected to ion exchange to obtain a resin solution (solid content: 20.43% by mass). To 3.45 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 0.82 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0496] <Comparative Example 51>

[0497] The resin obtained in Comparative Synthesis Example 51 was dissolved in propylene glycol monomethyl ether and then subjected to ion exchange to obtain a resin solution (solid content: 23.68% by mass). To 2.98 g of the resin solution were added 0.07 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.18 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.88 g of propylene glycol monomethyl ether of benzenesulfonate, 1.30 g of propylene glycol monomethyl ether acetate, 0.05 g of propylene glycol monomethyl ether, and 4.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0498] <Comparative Example 52>

[0499] The resin obtained in Comparative Synthesis Example 52 was dissolved in cyclohexanone and then subjected to ion exchange to obtain a resin solution (solid content: 34.12% by mass). To 1.65 g of the resin solution were added 0.06 g of propylene glycol monomethyl ether acetate containing 1% of a surfactant (Megaflux R-40 manufactured by DIC Corporation), 0.14 g of PL-LI (manufactured by Midori Chemical Co., Ltd.), and 2% by mass of pyridine. 0.71 g of propylene glycol monomethyl ether of benzenesulfonate, 0.67 g of propylene glycol monomethyl ether acetate, 2.22 g of propylene glycol monomethyl ether, and 2.55 g of cyclohexanone were dissolved and filtered through a polytetrafluoroethylene microfilter with a diameter of 0.1 μm to prepare a solution of a resist underlayer film forming composition.

[0500] [Dissolution test into resist solvent]

[0501] The solutions of the resist underlayer film-forming compositions prepared in Comparative Examples 51 and 52 and Examples 51 to 67 were applied to silicon wafers using a spin coater, and fired on a hot plate at 250° C. for 60 seconds or at 350° C. for 60 seconds to form resist underlayer films (film thickness 0.20 μm). These resist underlayer films were immersed in ethyl lactate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and cyclohexanone, which are solvents used for resists. These resist underlayer films were insoluble in these solvents.

[0502] [Measurement of optical constants]

[0503] The solution of the resist underlayer film forming composition modulated in Comparative Examples 51, 52 and Examples 51 to 67 was coated on a silicon wafer using a spin coater. The resist underlayer film (film thickness 0.05 μm) was formed by firing at 250° C. for 60 seconds or at 350° C. on a hot plate. For these resist underlayer films, the refractive index (n value) and optical absorption coefficient (also referred to as k value, attenuation coefficient) at a wavelength of 193 nm were measured using a spectroscopic ellipsometer. The results are shown in Table 4.

[0504] [Table 4]

[0505] Table 4 Refractive index n and optical absorption coefficient k

[0506]

[0507] [Determination of dry etching rate]

[0508] The etcher and etching gas used for the measurement of the dry etching rate were as follows.

[0509] RIE-10NR (manufactured by SAMU): CF4

[0510] The solutions of the resist underlayer film forming compositions prepared in Comparative Examples 51-52 and Examples 51-67 were applied to silicon wafers using a spin coater. The resist underlayer film (film thickness 0.20 μm) was formed by firing at 250° C. for 60 seconds or at 350° C. for 60 seconds on a hot plate. The dry etching rate was measured using CF4 gas as an etching gas, and the dry etching rates of the resist underlayer films of Comparative Examples 51-52 and Examples 51-67 were compared. The results are shown in Table 5. The dry etching rate ratio is the dry etching rate ratio of (resist underlayer film) / (KrF photoresist).

[0511] [Table 5]

[0512] Table 5 Dry etching speed ratio

[0513]

[0514] [Evaluation of embedding properties]

[0515] The embedding property was confirmed in the dense pattern area of ​​SiO2 substrate with a film thickness of 150nm, a groove width of 50nm and a spacing of 100nm. After the resist underlayer film forming composition modulated in Comparative Examples 51, 52 and Examples 51 to 67 was coated on the above-mentioned substrate, it was fired at 250°C for 60 seconds or at 350°C for 60 seconds to form a resist underlayer film of about 200nm. The flattening property of the substrate was observed using a scanning electron microscope (S-4800) made by Hitachi High Tech Nologics, and the presence or absence of the resist underlayer film forming composition filling into the pattern was confirmed (Table 6).

[0516] ○ indicates good, and × indicates bad.

[0517] [Table 6]

[0518] Table 6 Evaluation of embedding performance

[0519]

[0520] [Coating test on uneven substrates]

[0521] As a coating test on a high-low substrate, a SiO2 substrate with a film thickness of 200nm was used to compare the coating film thickness in an open area (OPEN) without a pattern and a dense pattern area (DENSE) with a groove width of 50nm and a spacing of 100nm. After the resist underlayer film forming composition modulated in Comparative Examples 51, 52 and Examples 51 to 67 was applied to the above-mentioned substrate, it was calcined at 250°C for 60 seconds or calcined at 350°C for 60 seconds to form a resist underlayer film of about 150nm. The flattening property of the substrate was observed using a scanning electron microscope (S-4800) manufactured by Hitachi HiTech Nologiz (Strain), and the film thickness difference between the groove area (pattern part) and the open area (no pattern part) of the high-low substrate was measured (the coating height difference between the groove area and the open area is called deviation (bias)), thereby evaluating the flattening property. Here, the so-called planarization property means that the difference in film thickness (Iso-dense deviation) of the coated material existing on the part with pattern (groove area (pattern part)) and the part without pattern (open area (no pattern part)) is small (Table 7). Specifically, Figure 1 (ba) is the Iso-dense deviation. In the figure, a is the depth of depression of the coating film at the center of the dense space, b is the depth of depression of the coating film at the center of the open area, c is the depth of the initial space in the high-low substrate used, d is the coating film, and e is the high-low substrate.

[0522] [Table 7]

[0523] Table 7 Evaluation of planarization

[0524]

[0525] Industrial Availability

[0526] According to the present invention, there is provided a resist underlayer film-forming composition which exhibits high etching resistance, good dry etching rate ratio and optical constants, has good coverage even on a so-called uneven substrate, has a small film thickness difference after embedding, and can form a flat film. In addition, according to the present invention, there is provided a method for producing a polymer suitable for the resist underlayer film-forming composition, a resist underlayer film using the resist underlayer film-forming composition, and a method for producing a semiconductor device.

Claims

1. A resist underlayer film-forming composition comprising: A reaction product of an aromatic compound (A) having 6 to 60 carbon atoms and a carbonyl group of a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; and Solvents, The cyclic carbonyl compound (B) contains 5% by mass or more of heteroatoms and is represented by the following formula (1): In the formula, X is O, NH or CH2, Ring Y is a three- to eight-membered ring which may have the following groups as substituents and which may be interrupted by a heteroatom, or a connected ring or condensed ring thereof, wherein the group is an alkyl group having 1 to 20 carbon atoms, a hydroxyl group, an oxo group, a carboxyl group, a cyano group, a nitro group, a sulfo group, an acyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 1 to 6 carbon atoms, an amino group, a glycidyl group, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms which may be substituted by a hydroxyl group or a carbonyl group and may be interrupted by an oxygen atom or a sulfur atom, and the cyclic carbonyl compound (B) does not contain a benzene ring, In the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two aromatic compounds (A). 2 . The resist underlayer film-forming composition according to claim 1 , wherein the cyclic carbonyl compound (B) has at least one hetero atom in one molecule.

3. A composition for forming a resist underlayer film, comprising: A reaction product of an aromatic compound (A) having 6 to 60 carbon atoms and a carbonyl group of a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; and Solvents, The cyclic carbonyl compound (B) is represented by the following formula (1): In the formula, X is CH2, Ring Y is a three- to eight-membered ring which may have as a substituent a group selected from the group consisting of an alkyl group having 1 to 20 carbon atoms, a hydroxyl group, an oxo group, a carboxyl group, a cyano group, a nitro group, a sulfo group, an acyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 1 to 6 carbon atoms, an amino group, a glycidyl group, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms, which may be substituted with a hydroxyl group or a carbonyl group and may be interrupted with an oxygen atom or a sulfur atom, or a connected ring thereof, In the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two aromatic compounds (A). 4 . The resist underlayer film-forming composition according to claim 1 , wherein the cyclic carbonyl compound (B) is an alicyclic compound. 5 . The resist underlayer film forming composition according to claim 1 , wherein the compound (A) contains one or more benzene rings, naphthalene rings, anthracene rings, pyrene rings, or a combination thereof. 6 . The resist underlayer film-forming composition according to claim 1 , wherein the compound (A) contains two or more benzene rings, naphthalene rings, anthracene rings, pyrene rings, or a combination thereof. 7 . The resist underlayer film-forming composition according to claim 1 , further comprising a cross-linking agent. 8 . The resist underlayer film-forming composition according to claim 1 , further comprising an acid and / or an acid generator. 9 . The resist underlayer film forming composition according to claim 1 , wherein the boiling point of the solvent is 160° C. or higher.

10. A resist underlayer film, characterized in that: A fired product of a coating film formed from the resist underlayer film forming composition according to any one of claims 1 to 9.

11. A method for manufacturing a semiconductor device, comprising the following steps: a step of forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition described in any one of claims 1 to 9; a step of forming a resist film on the resist underlayer film; a step of forming a resist pattern by irradiating and developing with light or electron beams; a step of etching the underlayer film using the resist pattern; and a step of processing the semiconductor substrate using the patterned underlayer film.

12. A method for producing a polymer for a resist underlayer film-forming composition, comprising the steps of: reacting an aromatic compound (A) having 6 to 60 carbon atoms with a carbonyl group of a cyclic carbonyl compound (B) having 3 to 60 carbon atoms; The cyclic carbonyl compound (B) contains 5% by mass or more of heteroatoms and is represented by the following formula (1): In the formula, X is O, NH or CH2, Ring Y is a three- to eight-membered ring which may have the following groups as substituents and which may be interrupted by a heteroatom, or a connected ring or condensed ring thereof, wherein the group is an alkyl group having 1 to 20 carbon atoms, a hydroxyl group, an oxo group, a carboxyl group, a cyano group, a nitro group, a sulfo group, an acyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 1 to 6 carbon atoms, an amino group, a glycidyl group, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms which may be substituted by a hydroxyl group or a carbonyl group and may be interrupted by an oxygen atom or a sulfur atom, and the cyclic carbonyl compound (B) does not contain a benzene ring, In the reaction product, one carbon atom of the cyclic carbonyl compound (B) is linked to two aromatic compounds (A).

Citation Information

Patent Citations

  • Material for resist lower layer film and method of forming pattern

    JP2004354554A

  • X-ray radiographic apparatus and control method thereof

    JP2017140193A

  • Silicon-containing resist underlayer film-forming composition containing cyclic amino group

    WO2009104552A1

  • Resist underlayer film-forming composition for EUV lithography containing condensation polymer

    CN103649835A

  • A polymer, composition, forming sacrificial layer and method for semiconductor device therewith

    TW201739784A